Providing Low-barrier Addiction Treatment Via a Telemedicine Consultation Service During the COVID-19 Pandemic in Los Angeles, County: An Assessment 1 Year Later. Issue 1 (15th January 2023) - Kennedy, Amy J.; George, James S.; Rossetti, Gina; Brown, Christopher O.; Ragins, Kyle; Dadiomov, David; Trotzky-Sirr, Rebecca; Sanchez, Gloria; Llamas, Herman; Hurley, Brian
Abstract : Background: Los Angeles County Department of Health Services provides medical care to a diverse group of patients residing in underresourced communities. To improve patients' access to addiction medications during the COVID-19 pandemic, Los Angeles County Department of Health Services established a low-barrier telephone service for DHS providers in March 2020, staffed by DATA-2000–waivered providers experienced with prescribing addiction medications. This study describes the patient population and medications prescribed through this service during its initial 12 months. Methods: We performed a retrospective evaluation of a provider-entered call registry for the telephone consult line. Information was collected between March 31, 2020, and March 30, 2021. The registry includes information related to patient demographics, the reason for visit, and which addiction medications were prescribed. We conducted descriptive statistics in each of these domains. Results: During the study period, 11 providers on the MAT telephone service logged 713 calls. These calls represented a total of 557 unique patients (mean age of 40 years, 75% male, 41% Latino, 49% experiencing homelessness). Most patients either had Medicaid insurance (77%) or were uninsured (20%). The most prescribed addiction medication was buprenorphine-naloxone (90%), followed by nicotine replacement therapy (5.3%), naltrexone (4.2%), and buprenorphine monotherapy (1.8%). Conclusion: A telephone addiction medication service is feasible to deliver low-barrier medications to treat addiction in underresourced communities, especially to individuals experiencing homelessness. This can mitigate but does not eliminate disparities in access to addiction medications for communities of color.